Risk factors with the occurrence of parasites and coliform in vegetables from an agroindustry - Martins Soto, Francisco Rafael; Vilela da Cruz, Jéssica; Rodrigues Lima, Laine; Silveira Duarte, Iolanda Cristina; Pereira Gazzinelli, Sandro Eugênio; Santos de Azevedo, Sérgio (Revista Ceres, 2025)
In this study, we evaluated the risk factors associated with the occurrence of total coliforms, thermotolerant coliforms, and intestinal parasite eggs in vegetables from an agroindustry in the city of Ibiúna – SP, Brazil. A questionnaire with 17 questions was applied to 24 producers to carry out a diagnosis of the risk factors and their posterior association or not with total coliforms, thermotolerant coliforms, and intestinal parasite eggs. The questions addressed mainly the production system, fertilizer used, source of the water used for irrigation, sanitization of the vegetables, and form of transport. For the investigation of total coliforms, thermotolerant coliforms, and intestinal parasite eggs, the samples were processed at the microbiology and parasitology laboratory of the Federal Institute of São Paulo, São Roque Campus. The results revealed that total coliforms were found in 100% of the investigated samples and thermotolerant coliforms were detected in 95.83% of the samples. There was a significant statistical association for the risk factor use of reservoir water, where there was release of wastewater and absence of sanitization of the vegetables at the moment of harvest in relation to the presence of thermotolerant coliforms. Intestinal parasite eggs were found in 33.33% of the samples.